Implementasi Nilai-Nilai Kewirausahaan Islami Di Pondok Pesantren Darul Falah Amtsilati - Rosada, Muhammad Musa Safa; Anwar, Aan Zainul (Jurnal Ilmiah Ekonomi Islam, 2026)
This study aims to describe the implementation of Islamic entrepreneurship values in the Darul Falah Amtsilati Islamic boarding school, focusing on the application of the values of honesty, trustworthiness, independence, creativity and Islamic work ethic in the management of pesantren business units such as minimarkets, building shops and Amtsilati Water drinking water companies. This research uses a qualitative method with a case study approach through observation, interviews and documentation of santri, administrators and ustadz who are directly involved in entrepreneurial activities. The results of this study show that Islamic entrepreneurship in this pesantren not only contributes to the economic independence of the pesantren, but also forms the character of entrepreneurial santri. However, this study found challenges, including the low interest of some santri in entrepreneurship and limited entrepreneurship training. The implications of this research confirm the importance of training programmes, as well as collaboration with external parties to strengthen the competitiveness of pesantren businesses. This research is expected to provide broad social benefits and strengthen the role of pesantren as centres of education and economic development based on Islamic values.